2020
DOI: 10.1021/acsomega.0c01582
|View full text |Cite
|
Sign up to set email alerts
|

Zeta Potential of Extracellular Vesicles: Toward Understanding the Attributes that Determine Colloidal Stability

Abstract: Extracellular vesicles (EVs), including exosomes and microvesicles (<200 nm), play a vital role in intercellular communication and carry a net negative surface charge under physiological conditions. Zeta potential (ZP) is a popular method to measure the surface potential of EVs, while used as an indicator of surface charge, and colloidal stability influenced by surface chemistry, bioconjugation, and the theoretical model applied. Here, we investigated the effects of such factors on ZP of well-characterized EVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
186
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(201 citation statements)
references
References 47 publications
14
186
0
1
Order By: Relevance
“…Therefore, differences found in the elastic modulus, together with the lower number of proteins present in the EVs of the epimastigote stage could be related to the higher content of sterol in the membrane of these forms [ 15 ]. Differential properties in stiffness and adhesion in metabolically different malignant (metastatic and non-metastatic) cell-derived EVs compared to non-malignant cells has been reported [ 33 ] and it is known that biomechanical properties of vesicles may play an important role in exocytosis and in intercellular transport [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, differences found in the elastic modulus, together with the lower number of proteins present in the EVs of the epimastigote stage could be related to the higher content of sterol in the membrane of these forms [ 15 ]. Differential properties in stiffness and adhesion in metabolically different malignant (metastatic and non-metastatic) cell-derived EVs compared to non-malignant cells has been reported [ 33 ] and it is known that biomechanical properties of vesicles may play an important role in exocytosis and in intercellular transport [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the electrical charge of the surface of EVs is reflected in the zeta-potential, it could be considered as a characteristic of the population of EVs. This electrical charge of the vesicles will depend, among others, on a series of factors: ionization of the components bound to the surface of the membrane, the chemistry of the grafted chains (if any), protonated states, inter and intramolecular bonds, presence of H bonds and the adsorption of ions of the electrolytes present in the solution in which they are found [ 33 ]. In our study, the slight differences shown in the standard deviation of the negative zeta-potential, higher in the case of EVs of E when compared to EVs of TCT, could indicate a wider distribution in the vesicles produced by these forms.…”
Section: Discussionmentioning
confidence: 99%
“… 9 The ZP of disperse systems is a measure of charge stability and affects all particle–particle interactions 10 and particle–medium interactions, including the tendency of the particles to aggregate. 11 A higher absolute ZP results in greater electrostatic repulsions between particles and minimizes their tendency for aggregates formation. EVs with ZP between −20 mV and +20 mV tend to aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications suggest that EVs physically interact to form dimers or larger clusters to regulate signaling in biological systems. 11 , 40 However, the relevance of aggregates formation and their effect on signal transfer to the target cells has not been explored yet, despite their crucial role in stability, pharmacokinetics, and release mechanism that are essential topics for developing drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, даже с чувствительностью мЭВ из культуральной жидкости от клеточных культур к детергентам не все ясно. Так, некоторые авторы считают, что, по крайней мере, неионные детергенты не растворяют мембрану мЭВ, а снижают дзета-потенциал частиц и таким образом снижают коллоидальную стабильность частиц в растворе, что может приводить, например, к выпадению частиц в осадок [8]. В некоторых работах для разрушения мЭВ из клеточных культур используют заведомо большую концентрацию детергентов, например 2% SDS [9].…”
Section: ведениеunclassified